Triarylboron‐Doped Acenethiophenes as Organic Sonosensitizers for Highly Efficient Sonodynamic Therapy with Low Phototoxicity (Adv. Mater. 49/2022). Issue 49 (8th December 2022) - Liu, Kanglei; Jiang, Zhenqi; Zhao, Fenggui; Wang, Weizhi; Jäkle, Frieder; Wang, Nan; Tang, Xiaoying; Yin, Xiaodong; Chen, Pangkuan
Abstract : Organic Sonosensitizers A new strategy of organic sonosensitizers based on boron‐doped acenethiophene scaffolds is presented by Zhenqi Jiang, Frieder Jäkle, Xiaodong Yin, and co‐workers in article number 2206594 . Ultrasound irradiation of water‐dispersible nanoparticle BAnTh‐NPs and BTeTh‐NPs can efficiently generate OH while exhibiting low phototoxicity. In vitro and in vivo studies indicate that boron‐doped acenethiophenes exhibit high SDT efficiency with excellent biocompatibility.